2019
DOI: 10.1101/567230
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into an alternative pathway for glycerol metabolism in a glycerol kinase deficientPseudomonas putidaKT2440

Abstract: 16Pseudomonas putida KT2440 is known to metabolise glycerol via glycerol-3-phosphate using 17 glycerol kinase an enzyme previously described as critical for glycerol metabolism (1). 18 However, when glycerol kinase was knocked out in P. putida KT2440 it retained the ability to 19 use glycerol as the sole carbon source, albeit with a much-extended lag period and 2 fold lower 20 final biomass compared to the wild type strain. A metabolomic study identified glycerate as a 21 major and the most abundant inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Upon phosphorylation by GarK, glycerate eventually enters the central metabolism, presumably as glycerate-2-phosphate. This conclusion is supported by the lack of growth of the ΔglpFKRD ΔgarK mutant and the results of a companion study (48), which used a comparative metabolome analysis of glycerol-growing cells of P. putida KT2440 and a ΔglpK deletion strain. The study found a dramatically increased glycerate concentration for the ΔglpK strain, whereas the concentrations of glyceraldehyde and glyceraldehyde-3-phosphate were in similar ranges for the two strains.…”
Section: Discussionmentioning
confidence: 78%
“…Upon phosphorylation by GarK, glycerate eventually enters the central metabolism, presumably as glycerate-2-phosphate. This conclusion is supported by the lack of growth of the ΔglpFKRD ΔgarK mutant and the results of a companion study (48), which used a comparative metabolome analysis of glycerol-growing cells of P. putida KT2440 and a ΔglpK deletion strain. The study found a dramatically increased glycerate concentration for the ΔglpK strain, whereas the concentrations of glyceraldehyde and glyceraldehyde-3-phosphate were in similar ranges for the two strains.…”
Section: Discussionmentioning
confidence: 78%
“…Given that the route further proceeds via glycerate and glycerate-2-phosphate, different cellular concentrations of these metabolites would be expected during growth on glycerol in a mutant that is not able to use the GlpFKRD pathway. Interestingly, a companion study to this work employed a metabolome analysis using glycerol-growing cells of P. putida KT2440 and a Δ glpK deletion strain, which can only use the proposed novel route via PedE and PedH (59). In their experiments, the authors observed that the glycerate concentration measured for the Δ glpK strain was dramatically increased compared to the wild type, whereas concentrations of glyceraldehyde and glyceraldehyde-3-phosphate were in the same range for both strains.…”
Section: Resultsmentioning
confidence: 99%